Respostas

  • Usuário do Brainly
2014-07-13T01:46:39-03:00
F)
21-x²=7-(x²+3x+2)

21-x²=7-x²-3x-2

-x² +x² +3x=7-2-21
 
           3x=-16
             x= \frac{-16}{3}

S={ \frac{-16}{3} }}

5)

 \frac{3(y+1)}{2} - \frac{( y^{2} +3y+2)}{5} = \frac{-2 y^{2} }{10}

mmc=10

15(y+1) -2(y²+3y+2)=-2y²

15y+15-2y²-6y-4=-2y²

-2y²+2y²+15y-6y=-15+4
                    9y=-11
                     y= \frac{-11}{9}

S={ \frac{-11}{9} }

6)
a)
 \frac{y+2}{3} - \frac{y+3}{2} =1

mmc=6

2(y+2)-3(y+3)=6

2y+4-3y-9=6
           -y=6+9-4
             -y=11
             y=-11
S={-11}

b)
 \frac{y+1}{3} - \frac{( y^{2}-y-6) }{2} = \frac{5- y^{2} }{2}

mmc=6

2(y+1)-3(y²-y-6)=3(5-y²)

2y+2-3y²+3y+18=15-3y²
-3y²+3y²+2y+3y=15-18-2

                 5y=-5
                   y=-1
S={-1}